1987
DOI: 10.1159/000226445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Melatonin on 9,10-Dimethyl-1,2-Benzanthracene-Induced Mammary Tumors in Female Holtzman Rats Exposed to Continuous Light

Abstract: Daily treatment of ‘functionally’ and surgically pinealectomized female Holtzman rats reared in continuous light (light: dark schedule, 24L:OD) with oral melatonin (100 pig/day/rat) initiated 30 days prior to and 90 days following 9,10-dimethyl-1,2-benzanthracene (DMBA) administration on day 55 of age, resulted in a highly significant suppression of mammary tumor incidence and prolongation of latency period of tumor appearance (p <0.001). An identical treatment schedule of melatonin to intact rats given DMBA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…The decreased level of prolactin, estradiol, lipid peroxides following Mel, NS and RA administration agrees with previous studies (Kothari 1987; Blask et al . 1991; Abou‐Issa et al .…”
Section: Discussionsupporting
confidence: 93%
“…The decreased level of prolactin, estradiol, lipid peroxides following Mel, NS and RA administration agrees with previous studies (Kothari 1987; Blask et al . 1991; Abou‐Issa et al .…”
Section: Discussionsupporting
confidence: 93%
“… suggested that high‐dose (300 mg/day = 5 mg/kg) melatonin delayed disease progression and extended survival through the reduction in oxidative damage in patients with amyotrophic lateral sclerosis. In addition, oral administration of melatonin (100 µ g/day/rat) via drinking water suppressed 7,12‐dimethylbenzanthracene‐induced mammary tumor growth . A number of clinical and basic studies are required to establish the optimal clinical dose of melatonin in certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…They found that melatonin reduced the number of tumors per rat in the ascending and descending colon when induced by DMH. Oral administration of melatonin via the drinking water was also reported to be effective in suppressing 7,12‐dimethylbenz(a)anthracene‐induced mammary tumor growth [119]. Finally, melatonin treatment induced apoptotic death in LNCaP cells via modulation of the p38 and JNK pathways [28].…”
Section: Melatonin’s Connection With Aging and Cancermentioning
confidence: 99%